Crystalline micro-nanoparticles enhance cross-linked hydrogels via a confined assembly of chitosan and γ-cyclodextrin. (15th December 2022) - Meng, He; Ye, Wenyan; Wang, Chunlei; Gao, Zeyu; Hu, Bingxuan; Wang, Caiqi
Abstract: Hydrogels constructed by traditional polymer networks usually have poor mechanical properties limiting their applications. Here, we proposed a new strategy for ionic interaction modulation of crystalline micro-nanoparticles (CMNPs) to enhance the mechanical properties of polyacrylamide hydrogels. CMNPs were formed via confinement assembly under an aggregated state based on host-guest interactions between chitosan-grafted polyethylene glycol (CS-PEG) and γ-cyclodextrin (γ-CD). Furthermore, the aggregation behavior of the CMNPs was achieved based on the ionic interaction of CS with citrate (Cit 3− ). These Cit 3− -regulated CMNPs were introduced into PAM hydrogels. The modulus (618.44 kPa, 67.6 times), fracture stress (1054.59 kPa, 25.3 times), and toughness (6.23 MJ m −3, 41.7 times) of the composite hydrogels were greatly improved without affecting the tensile properties (fracture strain, 1000 %). Finally, we further designed a strain sensor that could monitor human motion, and we verified its potential application in the field of wearable flexible electronics.